Skatole metabolites in urine as a biological marker of pigs with enhanced hepatic metabolism. (15th April 2016) - Brunius, C.; Vidanarachchi, J. K.; Tomankova, J.; Lundström, K.; Andersson, K.; Zamaratskaia, G.
Abstract : Boar taint is a quality defect in meat, related to accumulation of skatole and androstenone in male pigs. The levels of skatole and its main metabolites in plasma and urine samples were measured with a validated liquid chromatography-MS method and related to activity of hepatic cytochrome P450 (CYP450) in order to identify 'fast metabolizing' pigs. Urine ( n =46), blood ( n =12), liver ( n =25) and adipose tissue ( n =46) were sampled from a total of 46 entire male pigs. Skatole levels in fat were negatively correlated to CYP2E1 activity and positively to 3-hydroxy-3-methyloxindole (HMOI), indole-3-carboxylic acid (ICA) and 2-aminoacetophenone in urine. HMOI and ICA levels in urine were the best predictors of high skatole levels in fat. In summary, the present study provided further evidence for the key role of CYP2E1 in skatole metabolism and suggested that measurement of HMOI and/or ICA in urine might provide information about skatole levels in live pigs.